Occurrence of an incomplete C8 molecule in homozygous C8 deficiency in man (The Rockefeller University Press, 1981)
Sera from unrelated individuals with recurrent Neisserial infections lacked C8 hemolytic activity, but contained a protein that is antigenically related to C8. Immunochemical analysis revealed complete identity of the C8-related protein of all three sera and a marked antigenic deficiency compared with normal C8. The C8-related protein was isolated from serum by adsorption to immobilized anti-C8 IgG, elution with 3 M guanidine, and subsequent gel filtration. Upon sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis, the abnormal protein resembled the alpha-gamma subunit of normal C8 with respect to mobility and its ability to be cleaved upon reduction into the alpha and gamma chains. The beta chain present in normal C8 was absent. Sedimentation equilibrium analysis indicated a molecular weight of 86,000 for the abnormal C8 protein, which is identical to that of the alpha-gamma subunit of normal C8. Amino acid analysis revealed no significant difference between the abnormal C8 and normal alpha-gamma. Unlike normal C8, the abnormal protein did not bind to EAC1-7 or to SC5b-7; however, upon addition to the deficient serum of beta chain isolated from normal C8, hemolytic activity was restored and formation of SC5b-9 occurred. We concluded that the dysfunctional C8 protein in the three individuals' serum is identical to the alpha-gamma subunit of normal C8 and that this form of C8 deficiency is distinct from the C8 deficiencies previously reported in which the entire three-chain protein is lacking.